(untitled) (Chemical Engineering Research Bulletin, 2021)
In recent years algae has been receiving a lot of interest as an alternate source of biofuel. Fast growth and rich lipid content make algae a great candidate for producing eco-friendly and non-toxic biodiesel. The strain Chlorella vulgaris, has shown great potential as a source of oil. To optimize the mass culture of microalgae Chlorella vulgaris, it is necessary to develop growth kinetic model of Chlorella vulgaris. This work presents a comparative study on growth kinetics of Chlorella vulgaris in batch cultures in four different media, namely- CH, modified CH, Bold’s Basal (BB), and modified Bold’s Basal (BB). Spectroscopic analysis was supported by visual change of color in the algal biomass solution and the microscopic imaging, and was validated with dry cell mass measurement in this study. The data were analyzed to produce growth curves to find exponential phase for each medium. Exponential phases are the best period to harvest the culture. Hence the duration of exponential phase and the final biomass concentration at the end of exponential phase are two important parameters to determine the most suitable medium for mass culture. In this study the overall specific growth, doubling time and biomass productivity of Chlorella vulgaris for CH, modified CH, BB and modified BB media were measured. This study will help to find a suitable media to culture Chlorella vulgaris, a high lipid content algae in the local environment. The information can be used to design a system for mass culture of the strain for biodiesel production. Chemical Engineering Research Bulletin 21(2020) 133-138